2020
DOI: 10.1021/jacs.0c01365
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase N Activatable Fluorescent Probe for Tracking Metastatic Cancer and Image-Guided Surgery via in Situ Spraying

Abstract: The recurrence of malignant tumors is mostly caused by incompleted surgical resection. Especially, it is difficult for surgeons to detect and accurately remove metastatic tumors by predominantly using visual examination and palpation owing to the lack of effective means to specifically distinguish the boundary range between normal and tumor tissues. Thus, the development of activated fluorescent probe with superior tumor-to-normal (T/N) tissue ratios is particularly urgent in clinics. In view of CD13/aminopept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(149 citation statements)
references
References 62 publications
0
149
0
Order By: Relevance
“…6 This latter condition can be met by using near-infrared fluorescence covering the first therapeutic window (650-900 nm), where both absorbance, light scattering and autofluorescence are low. 7 Viscosity, as the single-most important factor in diffusioncontrol processes, plays a vital role in chemistry and biological activities. 8 In fact, unusual variations in micro-viscosity of cell is associated with many human-diseases, such as diabetes, Alzheimer's disease, atherosclerosis and especially, cell malignancy.…”
Section: A Combined Viscosity-restricted Intramolecular Motion and Mitochondrial Targeting Leads To Selective Tumor Visualizationmentioning
confidence: 99%
“…6 This latter condition can be met by using near-infrared fluorescence covering the first therapeutic window (650-900 nm), where both absorbance, light scattering and autofluorescence are low. 7 Viscosity, as the single-most important factor in diffusioncontrol processes, plays a vital role in chemistry and biological activities. 8 In fact, unusual variations in micro-viscosity of cell is associated with many human-diseases, such as diabetes, Alzheimer's disease, atherosclerosis and especially, cell malignancy.…”
Section: A Combined Viscosity-restricted Intramolecular Motion and Mitochondrial Targeting Leads To Selective Tumor Visualizationmentioning
confidence: 99%
“…9 Aminopeptidase N (also named CD13) is a widely expressed type II membrane-bound metalloprotease involved in pleiotropic functions, such as cell adhesion, proliferation, and motility. 10 Recent research demonstrated that CD13 is a novel marker for semi-quiescent CSCs in HCC and is responsible for the chemoresistance. 11 Although CD13 may be a potential therapeutic target for alleviating drug resistance in HCC therapy, the potential role and underlying molecular regulation mechanism by which CD13 contributes to the sorafenib resistance remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently studies reported the correlation between sorafenib resistance and tumor cell subpopulations with stem/progenitor cell phenotypes in HCC, implicating that targeting these subpopulations might be a promising option for overcoming drug resistance in HCC 9 . Aminopeptidase N (also named CD13) is a widely expressed type II membrane‐bound metalloprotease involved in pleiotropic functions, such as cell adhesion, proliferation, and motility 10 . Recent research demonstrated that CD13 is a novel marker for semi‐quiescent CSCs in HCC and is responsible for the chemoresistance 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, activatable probes for the evaluation of the activity of APs, including leucine AP and aminopeptidase N (APN), have been reported. [ 101–104 ]…”
Section: Advances Of Enzyme‐activatable Optical Probesmentioning
confidence: 99%